2024
DOI: 10.5187/jast.2023.e20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of proteases on performance, carcass traits and gut structure of broilers fed diets reduced in protein and amino acids

Abstract: Comparative effects of proteases on performance, carcass traits and gut structure of broilers fed diets reduced in protein and amino acids Running Title (within 10 words)Effect of proteases in broiler diets reduced in protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Six treatments resulting from a 3 × 2 factorial arrangement of 3 dietary CP levels (17, 19, and 21%) and 2 levels of exogenous multiprotease (KEMZYME TM Protease, Kemin Industries, Des Moines, IA) supplementation (0 and 2,400 U/kg) were evaluated in a completely randomized design with seven replicates per treatment. The 2,400 U/kg equates to 300 g/t feed and is in line with the use of this protease in other studies ( Chandrasekar et al, 2017 ; De Leon et al, 2021 ; Wealleans et al, 2023 ). The multiprotease includes a combination of acid (pepsin type protease), neutral (metallo endo-peptidase), and alkaline (serine endopeptidase), proteases, produced by Aspergillus niger, Bacillus subtilis, and Bacillus licheniformis , respectively ( Lim et al, 2014 ).…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Six treatments resulting from a 3 × 2 factorial arrangement of 3 dietary CP levels (17, 19, and 21%) and 2 levels of exogenous multiprotease (KEMZYME TM Protease, Kemin Industries, Des Moines, IA) supplementation (0 and 2,400 U/kg) were evaluated in a completely randomized design with seven replicates per treatment. The 2,400 U/kg equates to 300 g/t feed and is in line with the use of this protease in other studies ( Chandrasekar et al, 2017 ; De Leon et al, 2021 ; Wealleans et al, 2023 ). The multiprotease includes a combination of acid (pepsin type protease), neutral (metallo endo-peptidase), and alkaline (serine endopeptidase), proteases, produced by Aspergillus niger, Bacillus subtilis, and Bacillus licheniformis , respectively ( Lim et al, 2014 ).…”
Section: Methodssupporting
confidence: 84%
“…However, it is possible to further improve the efficiency of nutrient utilization and digestibility by observing details such as accurate feed formulation close to broiler amino acid ( AA ) needs, improving the balance between protein and starch digestibility dynamics ( Moss et al, 2018 ; Chrystal et al, 2020 ; Liu et al, 2021 ), and adding exogenous enzymes that increase AA digestibility ( Pan et al, 2016 ; Borda-Molina et al . , 2019 ; Wealleans et al, 2023 ). Improvements in apparent ileal AA digestibility in broilers are reported to result in improvements in growth performance and reduced N excretion and may improve overall gut health due to reduced putrefaction in the distal intestine ( Cowieson et al, 2017 ; Cardinal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…When indispensable AA was supplemented in the LP diet to meet requirements, reducing dietary CP from 20.0% to 17.0% did not lower BW, BWG, FI, and G:F. Previous studies have demonstrated that dietary CP can be practically reduced by up to 3% without adversely affecting growth performance [4,[32][33][34][35], corroborating this current finding. However, reducing dietary CP may be able to impair growth performance, even with indispensable AA supplementation in the LP diet.…”
Section: A C C E P T E Dsupporting
confidence: 88%
“…The improvements in nutrient digestibility are caused by reduced intestinal viscosity and the breaking down of the arabinoxylan backbone into arabinose and xylose at different segments of the broiler gastrointestinal tract [3]. As earlier reported, both the nature and the level of NSP present in wheat bran may also impair endogenous amino acid release and suppress amino acid digestibility [27]. The current findings, along with those results from Esmaeilipour et al [28] suggest that xylanase can reduce nutrient entrapment and increase the digestibility of mostly starch and protein at the early stages of a chick's life.…”
Section: A C C E P T E Dmentioning
confidence: 87%